Identification of two nuclear subclasses of the adenovirus type 5-encoded DNA-binding protein. - Voelkerding, K (1986)
The synthesis, accumulation, and subcellular distribution of the adenovirus serotype 5 DNA-binding protein (DBP) has been examined during the infectious cycle in HeLa cells. With the onset of viral DNA replication and entry into the late phase, two nuclear subclasses of DBP are distinguishable by immunofluorescence microscopy and can be separately isolated by in situ cell fractionation. The first subclass, represented by diffuse-staining DBP, is released by the addition of 1% Nonidet P-40-150 mM NaCl. The second subclass of DBP, which is sequestered into intranuclear globular structures, requires a high ionic strength (2 M NaCl) for extraction and appears to be associated with centers of active viral DNA replication. This association is based on the observations that: DBP within the globules and viral DNA, as detected by in situ hybridization, form identical structures that colocalize within the nuclei of infected cells, the formation of DBP globular structures requires the onset and continuation of viral DNA replication, and once formed, the globular structures can be perturbed by modulating viral DNA synthesis.